NORMATIVE JURIDICAL ANALYSIS OF FORGERY OF LETTERSIN AN AUTHENTIC DEED COMMITTED BY NOTARIES - Kameswari Perbawa, Nidya (Kertha Semaya : Journal Ilmu Hukum, 2024)
This study examines the legal framework for notaries who commit acts of forgery of letters in an authentic deed based on the decision of the Denpasar District Court Number 147/Pid.B/2022/PN Dps. As public officials with the authority to create authentic deeds, notaries are expected to serve the public interest by providing a service that avoids forgery and ensures the authenticity and legal status of the deeds they create. This study centers its objective at examining the legal basis provided to Notaries who have committed acts of forgery of authentic deeds they have prepared. The research method employed is the normative legal research method with a normative juridical approach. The results of the description and analysis of this research indicate that the criminal act committed by the defendant, for forgery of letters in an authentic deed has fulfilled the elements of the  criminal act of forgery of letters in an authentic deed committed by a Notary in accordance with Article 264 of the Criminal Code and Article 55, paragraph (1). In view of the above, it is appropriate to impose the legal sanctions that have been applied to the defendant in respect of violations of the code of ethics contained in the Notary Position Law. This includes the imposition of a prison sentence of three years. It is also appropriate to impose the repressive steps or sanctions used in imposing punishment on the defendant .